Reflection Method in Shaping Student Character on Islamic Education: Ibn Thufail's Perspective - Muna, Shela Khotijatul; Suhaili, Suhaiella; Gumilang, Randi Muhammad (TATHO: International Journal of Islamic Thought and Sciences, 2024)
Facts about the character of students who are not good are still found; however, solutions to these problems must continue to be done as a process of educating students on an ongoing basis. Such is the case with this study, Qualitatively descriptive, which aims to describe the implementation of the reflection method in Islamic Religious Education subjects in helping student character at Hidayatul Mustafidin High School, Kudus, Indonesia, from the perspective of Ibn Thufail's thought. In-depth interviews involve extracting data, observing, taking documentation, and validating it with triangulation. The data were analyzed through data reduction, presentation and verification/conclusion stages. Applying Ibn Thufail's perspective reflection method in PAI subjects in shaping student character at Hidayatul Mustafidin High School is carried out in several ways, including holding regular reflection sessions, and PAI teachers provide direction and motivation to students. In the discussion groups in the classroom, students are given one theme and then asked to discuss and write a report on the results of the discussion. Furthermore, they are holding field trips in the form of nature tadabbur activities. These activities certainly provide benefits to students, especially in shaping character. Students become aware of what has been done, how to improve poor attitudes, understand each other's characters, and increase gratitude and an embedded attitude of responsibility for what has been done.